Penguatan Inklusi Keuangan pada Industri Kreatif Berskala Mikro Kecil di Sumatra Barat - Fitriana, Widya; Rustiadi, Ernan; Fauzi, Akhmad; Anggraeni, Lukytawati (Jurnal Ekonomi dan Pembangunan Indonesia, 2018)
Creative industry is a strategic sector of national development. Lack of capital is a major obstacle to its development. This study analyzes financial inclusion of micro small creative industries (MSCI) relating to access and loan use. Both logit and Tobit models were employed for 1,367 MSCI from micro small survey data 2014. This study proved that women entrepreneurs who are less educated, limited asset and located in rural area tend to have greater constraints in financial inclusion. This study recommend the importance of financial education for women entrepreneurs in rural areas and expansion of internet uses and conduct digital finance.